Caribbean Report 16-03-1990 - Crosskill, Hugh (anchor); Timmins, Jerry (correspondent); Scoon, Paul (interviewee); Brathwaite, Nicholas (interviewee); Stainer, Robin (analyst); Porter, Adrian (correspondent) (The British Broadcasting Corporation, 1990)
Nicholas Brathwaite is sworn in as the new Prime Minister of Grenada after three days of wrangling between the successful parties at Tuesday’s general elections. The National Democratic Congress won seven of the 15 seats and the recent support of Ben Jones and Alleyne Walker of the Grenada National Party provides a clear majority for the new government. Ben Jones will be appointed as the Deputy Prime Minister. The new prime minister comments on the accommodation with the GNP, the immediate tasks of the government and the new era of change in Grenada. The second segment highlights the emergency meeting of the Guyana Support Group in response to the cut back of US financial aid to Guyana. Following the stories of interest to the Caribbean appearing in the British press, the British fruit importers assess the quality of banana imports from the Dominican Republic.
1. Nicholas Brathwaite sworn in as the new Prime Minister of Grenada. Jerry Timmins reports from St. Georges, includes comments from Paul Scoon, Governor General. Telephone interview with the new Prime Minister of Grenada, Nicholas Brathwaite (00:00-07:31)
2. Financial News. Robin Stainer, commodity analyst comments on the supply of sugar on the world market (07:32-09:01)
3. Guyana Support Group holds an emergency meeting in Washington. Adrian Porter reports from Washington (09:02-11:32)
4. Stories of Caribbean interest appearing in the British press (11:33-13:37)
Keywords: Elections -- Grenada.; Coalition governments -- Grenada.; Grenada -- Politics and government.; Prime ministers -- Election -- Grenada.; Economic assistance -- Guyana.; Banana trade -- Dominican Republic.; Guyana Support Group.